FACTORS RELATED OF COVID-19 IN THE WORK AREA OF THE MAKASAR DISTRICT HEALTH CENTER - Nadratul Laila; Asyifa Robiatul Adawiyah; Izattul Azijah; Nur Apriyan (Indonesia Epidemiological Journal, 2022)
COVID-19 is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). COVID-19 can be transmitted to all age groups, but the elderly who have previous diseases such as cardiovascular disease, diabetes, hypertension, and chronic obstructive pulmonary disease will worsen the COVID-19 disease. Therefore, factors related to COVID-19 are needed to prevent and control COVID-19. The purpose of this study was to determine the factors related to the incidence of COVID-19 in the working area of ​​the Makassar District Health Center in 2021. This type of research was descriptive cross-sectional. The population of this study is the community in the Makassar District Health Center with a sample of respondents aged 17-60 years with a total of 140 respondents. The sampling method was using consecutive sampling techniques through an online google form questionnaire. Data collection was carried out on 23 June -1 July. Data analysis used univariate and bivariate analysis. The results showed that most of the respondents had good knowledge, family roles, behavior, and lifestyle. There is a relationship between gender (p-value = 0.048), education (p-value = 0.014) and behavior (p-value = 0.040) with the incidence of COVID-19. While the unrelated factors are age, occupation, income, comorbidities, BMI status, knowledge, family roles, and lifestyle. It is hoped that the public health center will maximize health promotion and 3T, hold socialization of the distribution of masks, vitamins, and other drugs to increase immunity.